Applying Differentiated Instruction to Enhance Student Engagement and Learning Outcomes in Integrated Social Studies in Junior High School - Nur Intang; Elpisah Elpisah; Hartini Hartini (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This research is classroom action research that aims to improve the learning outcomes of Integrated Social Sciences through the application of differentiated learning in grade VII students of UPT SMPN Satap Pulo Bembe No. 29 Selayar Islands. The subject of this study is a student of grade VII UPT SMPN Satap Pulo Bembe No. 29 with a total of 12 students consisting of 7 male students and 5 female students. This research was carried out in two cycles, namely cycle I which was carried out 3 meetings (the first and second meetings for the learning process and the third meeting for Integrated Social Studies learning outcome assessment activities) and cycle II was also carried out 3 meetings. The two cycles were carried out for 2 months plus summarizing all existing research results. The results of the study show that the application of differentiated learning has succeeded in significantly improving student learning outcomes. In the first cycle, 50% of students have not reached the completion score, but in the second cycle, the number of students who did not complete the score decreased drastically to only 8%, while the number of students who achieved the completion score increased to 92%. This shows that differentiated learning is effective in overcoming academic gaps between students and improving their achievement of learning outcomes. In addition to improving learning outcomes, differentiated learning has also been proven to be effective in increasing student activity. In the first cycle, the average student activity only reached 68%, showing that even though some students are already active, there are still many who lack participation. After the implementation of a more optimal differentiated learning strategy in cycle II, student activity increased significantly to 87%. This shows that the differentiated learning approach not only helps students in understanding the material, but also increases their engagement in the learning process. The application of differentiated learning in cycle II resulted in a significant increase in learning outcomes and student activity, which shows the success of this strategy in meeting the diverse learning needs of students.